Serat Wedhatama dan Kesempurnaan Hidup: Perspektif Teori Insan Kamil Ibnu Arabi - Alif Balya Mustofa Mustofa; Salwa Al Hassan; Izzatyl Auliya Rahmah; Moh. Hamid; Muhammad Reza; Muhammad Ali Fahruddin; Muhammad Tarobin (Pusat Riset Manuskrip, Literatur, dan Tradisi Lisan, 2026)
In the midst of a strengthening moral and spiritual crisis in contemporary society, the study of local wisdom is important to revitalize human values rooted in tradition. This research aims to analyze the concept of perfection of life in the Wedhatama Serat by KGPAA Mangkunegara IV and examine its relevance through the theory of Insan Kamil Ibnu Arabi. In particular, this study examines the spiritual and ethical teachings contained in each of the Wedhatama Serat Teachings, as well as comparing the concept of the main janma with the idea of a perfect human being in the philosophical Sufism tradition. The research uses a qualitative method based on library research with Wedhatama Serat as the primary data source, while literature on Ibn Arabi, the concept of insan kamil, and Javanese philosophy is used as a secondary source. The analysis is carried out through a comparative-philosophical approach to bring together the concept of ngelmu kasampurnan in the Javanese tradition with universal spirituality in Sufism. The results of the study show that the Wedhatama Serat not only contains moral teachings, but also offers a deep vision of human perfection through inner practice, lust control, ethics formation, and the principles of consciousness and vigilance. These values have substantive harmony with the concept of human beings, namely human beings who are able to reflect on divine attributes in their lives. The perfection of life in the Wedhatama Serat is understood not as a static condition, but as a continuous spiritual process towards closeness to God. These findings show the existence of an epistemological dialogue between Javanese spirituality and Ibn Arabi's Sufism, while affirming the relevance of cross-cultural spiritual humanism as a foundation for building a balance between the mundane and transcendental dimensions in modern life.